From Munich to Christchurch: International Sport and the Threat of Terrorism - Davies, Chris (Victoria University of Wellington Law Review, 2022)
The 1972 Munich Olympic Games is remembered for the terrorist attack which resulted in 11 members of the Israeli team being killed. It highlighted that sporting events and teams can be targeted by terrorists due to the high media profile that major sporting events attract. Since this time, high level security has been an important organising consideration for the Olympic Games, something that has increased since the September 11 attacks in the United States in 2001. Other sporting teams, namely the Togo national football team and the Sri Lanka national cricket team, have likewise been targeted. The international aspect of many sports requires extensive touring to other countries, and this has resulted in various touring teams being in places that have been terrorist targets, as the New Zealand national cricket team experienced in Pakistan. New Zealand is not a region of the world prone to terrorism problems, but the March 15 attack on a Christchurch mosque could have led to loss of life amongst the touring Bangladesh national cricket team. No region or country is free from potential terrorist attacks involving sporting teams.